STRATEGI PERUSAHAAN MEMPERLUAS USAHANYA, BOLEHKAH DENGAN BERHUTANG? - Wilchan Robain; Abdul Rahman (Jurnal Abdi Ilmu, 2021)
The purpose of this study was to look at the strategy of the company is expanding its business can be the debt allowed by commercial law and in the view of Islam, and is expected to be useful for businesses, especially Muslim businessmen to conduct business. The results of the analysis that the debt can be justified and should qualify that, the goods or services that are owed are the owners must be clear and purely lawful, the creditor does not link the debt problem to something else and does not hurt the debtor, the creditor should only intend to get the pleasure of Allah SWT by giving the debt properly and the goods or services that are deferred do not provide advantages or benefits to the debtors and must be civilized. Need more focused research and analysis to obtain concrete results and tangible mainly expected to be useful for businesses in conducting their business in the future without violating the norms of economic and religious.